News and Corporate Governance : What Dow Jones and Reuters Teach Us About Stewardship - World Bank (World Bank, Washington, DC, 2012)
Corporate governance in the media faces an intractable problem. There is an important public interest in the integrity of news, which is the lifeblood of an open society. Yet the shareholder value model of governance offers no guarantee that the integrity of news will be protected. Indeed, conflicts of interest abound in a business where dominant CEOs often put their own private interests before those of other shareholders, reflecting the principal/agent problem, as well as before those of society. In this paper Donald Nordberg, a former senior editorial executive at Reuters who also worked as a consultant for Dow Jones, explores the respective governance of these two media giants, which received bids last year respectively from Thomson Corp of Canada and Rupert Murdoch's News Corp. The perception that Rupert Murdoch had given in to pressure from the Beijing government to drop news channels from his company's television transmissions into China raised the issue of conflicts of interest very starkly for executives and journalists on the Wall Street Journal, the crown jewel of the Dow Jones group.